Deliart (Delivery Service) / Muhammad Adib Sahabudiin - Muhammad Adib, Sahabudiin (2020)
DELI-ART SDN BHD a business that took delivery concept and apply them to stationery business for convenient of people. The business also provides a delivery service of many kind of stationery items alike and sold around for customer like student and working people nearby Seri Iskandar area. The market are quite explorable. This are based from most of the students nearby having a hard time purchasing their stationery needs because of the strict curfew and no access to vehicle. The target market are quite a lot but only when academic session started. Then will decline when semester break started. On the competitive side, there is not really any similar like business to compare. But since it’s the first of it kind many people would not know about it. The profit of this business are coming from delivery charge of 10% from one purchased transaction. The profit estimated are high from October to January because of the academic session and estimated low between August – September and February – March because of semester break.